Analysis of colectomy rates for ulcerative colitis in pre‐ and postbiological eras in Lothian, Scotland. (17th February 2021) - Jenkinson, Philip W.; Plevris, Nikolas; Lyons, Mathew; Grant, Rebecca; Fulforth, James; Kirkwood, Kate; Arnott, Ian D.; Wilson, David; Watson, Angus J. M.; Jones, Gareth‐Rhys; Lees, Charlie W.
Abstract: Aim: Biological treatment is effective in maintaining remission in ulcerative colitis (UC), although the effect on colectomy rates remains unclear. In the UK the use of antitumour necrosis factor and anti‐α4β7 treatments for maintenance therapy in UC was restricted until 2015. The aim of this study was to describe the impact that this change in the prescribing of biologicals had on colectomy rates for UC. Method: All patients (adult and paediatric) with a diagnosis of UC who received maintenance biological treatment and/or underwent a colectomy in Lothian, Scotland between 2005 and 2018 were identified. Linear and segmental regression analyses were used to identify the annual percentage change (APC) and temporal trends (statistical joinpoints) in biological prescription and colectomy rates. Results: Rates of initiation of maintenance biological therapy increased from 0.05 per 100 UC patients in 2005 to 1.26 in 2018 ( p  < 0.001). Colectomy rates per 100 UC patients fell from 1.47 colectomies in 2005 to 0.44 in 2018 ( p  < 0.001). The APC for colectomy decreased by 4.1% per year between 2005 and 2014 and by 18.9% between 2014 and 2018. Temporal trend analysis (2005–2018) identified a significant joinpoint in colectomy rates in 2014 ( p  = 0.019). Conclusion: The use of maintenance biological therapy increased sharply following the change in guidance. This has been paralleled by a significant reduction in the rates of colectomy over the same time period.